ChemInform Abstract: Rapid Entry into Heterocycle‐Fused Benzylic Azepines and Azocines via Directed Metallation/Ring‐Closing Metathesis. Issue 46 (24th October 2013) - Moss, Thomas A.
Abstract Dienes (I), (III), and (V), are synthesized and applied in the ring‐closing metathesis reaction to afford a series of heterocyclic fused 2‐azocine derivatives (II), (IV), and (VI), respectively.